2017
DOI: 10.1177/0021998317742709
|View full text |Cite
|
Sign up to set email alerts
|

Garnet and Al-flyash composite under dry sliding conditions

Abstract: The dry sliding wear behaviour of LM 24 aluminum alloy composites reinforced with garnet particles was evaluated. Stir casting technique was used to fabricate the composites. A pin-on-disc wear-testing machine was used to evaluate the wear rate, in which an EN 24 steel disc was used as the counterface. Results indicated that the wear rates of the composites were lower than that of the matrix alloy and further decreased with the increase in garnet content. However, in both unreinforced and reinforced composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In wear study, it was revealed that the wear rate of the composites was decreased with the increase in garnet content. Also, wear rate was lower than that of the matrix alloy [16].…”
Section: Introductionmentioning
confidence: 80%
“…In wear study, it was revealed that the wear rate of the composites was decreased with the increase in garnet content. Also, wear rate was lower than that of the matrix alloy [16].…”
Section: Introductionmentioning
confidence: 80%
“…Advances in Civil Engineering between 1,400 and 1,900 kg/m 3 as specified by the code ASTM C 330 [44] and ASTM C 567 [45][46][47][48][49][50][51][52][53][54].…”
Section: Unit Weight Of Scc Mixesmentioning
confidence: 99%
“…e scenarios are produced by varying the most important main criterion weight obtained by Fuzzy AHP method. At the same time, the weights of the other criteria are adjusted using the following equation [30,31]:…”
Section: Sensitivity Analysismentioning
confidence: 99%